1919
DOI: 10.1056/nejm191912111812406
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Influenza-Pneumonia by Use of Convalescent Human Serum

Abstract: On September 28th, 1918, serum from convalescent influenzal pneumonia patients was used at my suggestion, in the treatment of this type of broncho-pneumonias at the Chelsea Naval Hospital on the service of Lt. Comm. MeGuire. The outcome in the treatment of 151

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…After sifting 1449 unique records against the protocol eligibility criteria, we identified 32 studies from 50 reports ( Supplementary Table 1 ). Three studies could not be obtained [ 17–19 ], although results from a study by Bass et al [ 17 ] were reported elsewhere [ 20 ], which enabled their inclusion. French (n = 1), German (n = 2), and Korean (n = 2) records were screened by single reviewers because of a lack of multilingual collaborators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sifting 1449 unique records against the protocol eligibility criteria, we identified 32 studies from 50 reports ( Supplementary Table 1 ). Three studies could not be obtained [ 17–19 ], although results from a study by Bass et al [ 17 ] were reported elsewhere [ 20 ], which enabled their inclusion. French (n = 1), German (n = 2), and Korean (n = 2) records were screened by single reviewers because of a lack of multilingual collaborators.…”
Section: Resultsmentioning
confidence: 99%
“…Three systematic reviews met our protocol eligibility criteria [ 7 , 21 , 22 ]. Data on 1327 patients from 6 case studies [ 23–28 ], 20 case series [ 8 , 17 , 20 , 29–45 ], 2 case-comparison studies [ 46 , 47 ], and 1 prospective cohort [ 48 ] were included. We identified 13 observational studies published between 1918 and 1920, which studied 980 patients who received a clinical diagnosis of influenza-associated pneumonia or Spanish influenza A (H1N1) infection [ 17 , 20 , 33–35 , 38–44 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most excluded studies (Appendix Table, available at www.annals.org) reported that use of influenza-convalescent blood products was beneficial (27)(28)(29)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). One large study at a U.S. Army recruit training hospital investigated the use of influenza-convalescent serum in patients with Spanish influenza but not pneumonia (27).…”
Section: Data From Excluded Studiesmentioning
confidence: 99%
“…No included study was identified solely from the citation review. We excluded 17 articles that were small case reports, were incomplete or noninterpretable, were written in a non-English language, or involved only patients with uncomplicated influenza (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Tables 1 and 2 show details from these studies, which ranged in size from 43 to 551 patients.…”
mentioning
confidence: 99%
“…The first use can be traced back between 1918 and 1920 during the Spanish Flu pandemic. 6 – 11 A meta-analysis was conducted by Luke et al regarding the effectiveness of CBP against Spanish influenza that involved eight studies and 1703 patients. 12 The study revealed significantly reduced mortality in CBP groups compared with untreated patients [16% versus 37% fatality; absolute risk difference 8% to 26%; pooled risk difference 21%, 95% confidence interval (CI): 15–27%].…”
Section: Convalescent Blood Productsmentioning
confidence: 99%